Pretplatnički radiosustavi TDMA u ruralnoj telekomunikacijskoj mreži - Bjele, Miroslav (Promet - Traffic&Transportation, 2012)
The paper deals with an effective and economic method of telecommunications network introduction in rural areas, by provision of digital subscriber radio-systems with multiple access (TDMA - Time Division Multiple Access). After a description of general characteristics of rural areas according to CCITT definition, special aspects have been reviewed that can be considered in our conditions. In addition to discussion of some special aspects of the rural telecommunications network planning procedure, due attention has been paid to a description of rural subscriber TDMA system planning. Furthermore the paper deals with general and technical specifications of the TDMA radio system and its application in the Croatian telecommunications system.